RETRACTED: Pengembangan Konten Interaktif untuk E-Learning di Lembaga Pendidikan Yayasan: Studi Kasus pada Course Moodle dengan Topik Presentasi Zen - Juistha, Adlin Astridiani (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This article was retracted due to unintentional double publication. The article was previously published in the Syntax Idea journal with the DOI [https://doi.org/10.46799/syntax-idea.v5i10.2983]. The duplication occurred as a result of miscommunication during the submission process, where the manuscript was submitted to multiple journals simultaneously without the knowledge of the authors and editorial teams. This retraction is issued to maintain the integrity of the scholarly record and uphold ethical standards in academic publishing. This research focuses on developing interactive media content for an e-learning course, specifically designed for teachers at Pandu Pertiwi Foundation. The objective is to equip them with tools to create engaging Zen-based learning presentations. The methodology adopted is Research and Development (R&D) using the ADDIE model, modified to include analysis, design, development, and implementation stages. During the development stage, the content underwent two cycles of evaluation by experts in material, learning design, and learning media. The implementation stage involved trials with three teachers, representing the end-users, to assess the content's suitability and applicability. The findings from these expert and user trials demonstrate that the H5P interactive content developed is practical and suitable for use in educational settings, offering valuable insights into the effective use of interactive media in e-learning environments.